Chemoselective Polymerization of Polar Divinyl Monomers with Rare-Earth/Phosphine Lewis Pairs - Pengfei Xu; Lei Wu; Liqiu Dong; Xin Xu (Molecules, 2018)
This work reports the chemoselective polymerization of polar divinyl monomers, including allyl methacrylate (AMA), vinyl methacrylate (VMA), and 4-vinylbenzyl methacrylate (VBMA), by using simple Lewis pairs comprised of homoleptic rare-earth (RE) aryloxide complexes RE(OAr)3 (RE = Sc (1), Y (2), Sm (3), La (4), Ar = 2,6-tBu2C6H3) and phosphines PR3 (R = Ph, Cy, Et, Me). Catalytic activities of polymerizations relied heavily upon the cooperation of Lewis acid and Lewis base components. The produced polymers were soluble in common organic solvents and often had a narrow molecular weight distribution. A highly syndiotactic poly(allyl methacrylate) (PAMA) with rr ~88% could be obtained by the scandium complex 1/PEt3 pair at −30 °C. In the case of poly(4-vinylbenzyl methacrylate) (PVBMA), it could be post-functionalized with PhCH2SH. Mechanistic study, including the isolation of the zwitterionic active species and the end-group analysis, revealed that the frustrated Lewis pair (FLP)-type addition was the initiating step in the polymerization.